P1_6 Golden Delivery - Dexter, Katie; Connors, Riley; Argyle, Joshua; Scoular, Cameron (Physics Special Topics, 2012)
This article investigates the magnitude of the magnetic field gradient required to transport a gold nanoparticle of 1.9nm in diameter through the cardiovascular system. As an upper limit, the gradient calculated to overcome the blood flow velocity in the aorta was calculated by setting the force from the magnetic field gradient to be larger than or equal to the viscous drag from the blood. This yielded a magnetic field gradient of 1.3x1013Tm-1 which is far higher than what is available at present. The effects of such a high magnetic field gradient on the biological processes in the body must also be considered as haemoglobin, for example, contains iron.